Pengaruh Latihan Resistance Band dalam Meningkatkan Daya Tahan Otot Tungkai Atlet Futsal AAFI Jayapura - Pamungkas Yulian Effendi; Swandika Pinem; Muhammad Fitrah Mubarak; Abdul Bashir Nur Hasani; Fahmi Fadhil (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aimed to determine the effect of resistance band training on improving leg muscle endurance in futsal athletes at AAFI Jayapura. The method used was a pre-experimental design with a one group pretest-posttest design, involving 15 AAFI Jayapura futsal athletes selected through purposive sampling technique. The test instrument used in this study was a squat test to measure endurance, and the data were analyzed using normality and homogeneity tests as prerequisite tests, followed by a paired t-test and an analysis of the mean increase. The results showed that: (1) the research data were normally distributed and homogeneous; (2) there was an increase in the mean leg muscle endurance of futsal athletes from 68.87 at pre-test to 74.07 at post-test; (3) the paired t-test result showed a significance value of 0.000 < 0.05; and (4) there was a significant effect of resistance band training on the improvement of leg muscle endurance. The conclusion of this study is that resistance band training has a significant effect on improving leg muscle endurance in AAFI Jayapura futsal athletes. Keywords: Leg Muscle Endurance, Futsal, Resistance Band Training